Aplikasi Aljabar Geometris Pada Teori Elektrodinamika Klasik - Purwanto, Joko (Jurnal Fourier, 2012)
In this paper geometric algebra and its aplication in the theory of classical electrodynamic willÂ  be studied. Geometric algebra provide many simplification and new insight in the theoretical formulation and physical aplication of theory. In this work has been studied aplication of geometric algebra in classical electrodynamics especially Maxwellâs equations. Maxwellâs equations was formulated in one compact equationÂ ÃF=J. The various equation parts are easily identified by theirÂ  grades.